2012
DOI: 10.1155/2012/946943
|View full text |Cite
|
Sign up to set email alerts
|

The Key to Unlocking the Chemotherapeutic Potential of PPARγLigands: Having the Right Combination

Abstract: Despite extensive preclinical evidence that peroxisome proliferator-activated receptor (PPAR)γ activation protects against tumourigenesis, results from a few clinical trials using PPARγ ligands as monotherapy show modest success. In spite of this, several groups reported exciting results with therapeutic regimens that combine PPARγ ligands with other compounds: chemotherapeutic agents, retinoid x receptor (RXR)α agonists, statins, or cell-to-cell signaling molecules in preclinical cancer models and human trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 100 publications
(104 reference statements)
1
18
0
Order By: Relevance
“…This suggests activation of signaling within other PPARγ‐expressing cells associated with, or near, the mammary gland may contribute to this protective effect, and that activation of normal PPARγ signaling in other PPARγ‐expressing cells common to both strains is chemotherapeutic. This is consistent with reports suggesting that, for some parameters, combination antitumor therapies including PPARγ activators may be beneficial …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This suggests activation of signaling within other PPARγ‐expressing cells associated with, or near, the mammary gland may contribute to this protective effect, and that activation of normal PPARγ signaling in other PPARγ‐expressing cells common to both strains is chemotherapeutic. This is consistent with reports suggesting that, for some parameters, combination antitumor therapies including PPARγ activators may be beneficial …”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with reports suggesting that, for some parameters, combination antitumor therapies including PPARg activators may be beneficial. 32 Although no genotypic difference in median mammary tumor volumes was observed for either treatment, cotreatment with ROSI significantly decreased pooled malignant tumor volumes versus those from DMBA only-treated mice. This is consistent with studies showing PPARg activation suppresses carcinogen-induced mammary tumor growth in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…PPARγ is implicated in a wide variety of biological processes including adipogenesis, glucose metabolism, inflammation and tumorigenesis, and it is the molecular target of the thiazolidinedione (TZD) class of antidiabetic drugs including pioglitazone and rosiglitazone [51]. It has been shown that TZDs suppress the growth of several cancer lines in vitro and in vivo , and lines of preclinical evidence supports the antineoplstic effects of PPARγ agonists; however, results from clinical trials show modest success [52]. Recently, the use of pioglitazone for type 2 diabetes mellitus is reportedly associated with an increased risk of bladder cancer [53], suggesting a context-dependent, bidirectional effect of PPARγ on tumorigenesis, which is in accordance with its cell-specific effect on E 3 skipping (Fig.5), as well as the notion that both decreased and increased REST activity may contribute to tumorigenesis [18], [19].…”
Section: Discussionmentioning
confidence: 99%
“…All these findings suggest that a combination of demethylating agents and PPARγ agonists might be a useful therapeutic strategy in high‐risk MF patients. Future drug discoveries could give interesting perspectives in this field …”
Section: Discussionmentioning
confidence: 99%